The Symbolic Interpretation of Quraish Shihab on The Hadith of Women's Creation - Majid, Abdul (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2023)
The complete negation of misogynistic hadiths towards women is still not possible due to a textual and non-comprehensive understanding of the hadiths. This article aims to address this issue by presenting an analysis of Quraish Shihab's interpretation of the hadith regarding the creation of Eve from Adam's curved rib bone and differentiating his view from several other commentators. Using a literature review approach, this study shows that the term "curved rib bone" is not intended to disrespect women but merely as an illustration. Philosophically, the curved rib symbolizes women's inherent nature, which, when hardened, makes it difficult for men to straighten it out. This depiction aims to make men aware of and understand women's nature and to develop a wise attitude towards them. Quraish Shihab's ideas can be a recommendation for understanding hadiths with misogynistic nuances so that biases in understanding and actions towards women can be minimized effectively.